Pegaruh Partisipasi Anggota Terhadap Keberhasilan Koperasi Simpan Pinjam Di Desa Pengurung Kabupaten Kaur - Akmal, Samsul; Kasdi, By (Jurnal Adminitrasi Bisnis Nusantara, 2022)
With the development of business activities, so that the management of cooperatives is carried out professionally, it will be even greater. Professional management requires the existence of a good accountability system and relevant and reliable information for decision-making in planning and controlling cooperatives. One of these efforts is the development of the information system needed to grow cooperatives through accounting, in particular formulating financial accounting standards for cooperatives in the preparation of their financial statements. To measure the success of cooperatives, it is necessary to have a participation test and a market test, both of which illustrate that cooperatives must have a potential competitive advantage with others. capacity building and the role of cooperatives in Pengurung Village, Kinal District, Kaur Regency. in accordance with the interests of society in general, and the interests of members in particular